Disintegrated Impact of Trade Openness on Income Inequality: Empirical Evidence from Bangladesh - Chowdhury, Munem Ahmad; Nijhum, Hafsa Rahman; Uddin, Kazi Mohammed Kamal (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">There have been many studies on the relationship between trade and income inequality, but very few of them have distinguished the idea of trade by export and import. For this reason this study is conducted to see how the income inequality of Bangladesh get impacted with the presence of import and export separately. ARDL bound test is used to inspect whether they possess long run relation with income inequality for the period of 1975 to 2016. Thereupon export has been found to be widening the income gap in the long run. Though import improves the situation by abating the gap, it is not significant enough. Besides that other imperative macroeconomic variables are used to condense the omitted variable bias and their outcomes akin to the theory for developing country aspect. Furthermore, models like FMOLS, DOLS and CCR are used for ensuring the robustness of the result and other diagnostic tests support the validity of the result. Moreover policies related to labor welfare need to be set in a manner so that minimum wage allows a worker to lead a healthy life which will help keeping him or her productive. In addition, correspondent authority should frame the policies to diversify the export sector to give the opportunity to small entrepreneurs a chance to enter by providing the convenient environment.